Ecclesiastics and Economics: Poor Priests, Prosperous Laymen, and Proud Prelates in the Reign of Richard II - McHardy, Alison K. (Studies in church history, 1987)
It is a truth widely recognized, though perhaps insufficiently emphasized, that late-medieval England contained large numbers of unbeneficed clergy. The difficulty of studying such men lies in their elusiveness; they made little impact on the obvious source for a study of the English Church during this period, the bishops’ registers (apart from their appearances in the ordinations lists), for these are essentially concerned with benefices and benefice-holders. There is, however, one class of material which tells us much about the unbeneficed, namely the assessments made in connection with clerical poll-taxes. Levied in the years 1377, 1379, 1380, and 1381, these poll-taxes demanded what was virtually a clerical census on each occasion. The resulting returns are a boon to church historians and provide an unparalleled amount of information about the unbeneficed clergy, described in these documents as ‘chaplains’ and ‘clerks’. If we are to have a realistic picture of the late-medieval Church, the unbeneficed should receive more attention. Moreover, it is suggested that an examination of this class can throw light on the relationship between the Church and wealth during this period.